2006
DOI: 10.2174/092986606776819628
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Halophilic Nucleoside Diphosphate Kinase Sequence to the Heat Stability of Chimeric Molecule

Abstract: A halophilic nucleoside diphosphate kinase from a moderate halophile, Halomonas sp. 593 (593NDK), was found to be resistant to heat treatment, as indicated by the high level of activity recovery after heating at high temperatures. This is due to reversibility of thermal unfolding, not the high melting temperature, of the protein. The highly homologous NDK from non-halophilic organism, Pseudomonas aeruginosa, showed instability against heat treatment. Chimeric molecules consisting of each half of these two NDKs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
1
8
0
Order By: Relevance
“…The construction of chimeric proteins from HaNDK and PaNDK was described previously [13]. pET593Pandk encodes chimeric NDK consisting of N‐terminal half of HaNDK followed by C‐terminal half (71th–143th residues) of PaNDK (Ha/Pa‐NDK chimera).…”
Section: Methodsmentioning
confidence: 99%
“…The construction of chimeric proteins from HaNDK and PaNDK was described previously [13]. pET593Pandk encodes chimeric NDK consisting of N‐terminal half of HaNDK followed by C‐terminal half (71th–143th residues) of PaNDK (Ha/Pa‐NDK chimera).…”
Section: Methodsmentioning
confidence: 99%
“…The apparent molecular mass of His-KvSBD12 on SDS-PAGE (14% Laemmli gel) was ∼40 kDa, which was much higher than the true molecular mass, 23 kDa. This slow mobility on SDS-PAGE is one of the characteristics of halophilic proteins [29], due to abnormally weak SDS binding [30]. A single domain KvSBD1 with amino-terminal hexa-His-tag (His-KvSBD1, Fig.…”
Section: Expression and Purification Of Kvsbdmentioning
confidence: 99%
“…NDK from various organisms have been studied, including a moderately halophilic bacterium, and purification of NDK from Halomonas sp. 593 (HaNDK) and cloning and expression of HaNDK gene in E. coli with N‐terminal His‐tag have been reported (Yonezawa et al , 2001, 2003; Tokunaga et al , 2006). The database search of primary structures revealed that NDK from P. aeruginosa PAO1 (PaNDK) shows an extensive sequence similarity (78% identity and 89% similarity) to HaNDK.…”
Section: Introductionmentioning
confidence: 99%